Partnership throughout the ages: The coevolution of the transcriptional regulators LEUNIG and SEUSS in the green plant lineage - Garrecht, Julian Vincent; Justus Liebig University Giessen (My University, 2026)
The LEUNIG (LUG) and SEUSS (SEU) families of transcriptional regulators are centralmodulators of angiosperm development, with relevance lower formation, developmentof male and female gametangia, embryo development, and general plant growth. Theirinteraction forms a regulatory platform, bringing transcription factors and histone mod‐i iers together to both activate and repress target gene expression, thus creating a vastgene regulatory network. Interestingly, both families are deeply conserved, being presentin all land plant lineages and in many streptophyte algae, raising questions about whenthe origin of the LUG – SEU protein module, about their functions outside of angiosperms,and how the module evolved to govern various critical reproductive processes. This dis‐sertation demonstrates that the protein interaction between these two families, and withthe MADS‐box transcription factor family, evolved at least 800 million years ago in thestreptophyte algae, an that LUG and SEU exhibit a strong coevolution ever since. Theyare shown to function as gene regulatory hubs that, among other things, evolved along‐side the MADS‐box proteins to regulate multiple aspects of lower development and an‐giosperm reproduction, in concert with functions in stress response and phytohormonesignaling. Furthermore, the functions of LUG homologs in the moss Physcomitrium patenswere studied, revealing their connections to a critical developmental transition in mosses,and to the regulation of the auxin signaling pathway of land plants.
Keywords: LEUNIG; SEUSS; Protein interaction; Physcomitrium patens; Plant evolution; Plant development; ddc:570